Theoretical design and construction of a Doppler laser velocimeter for the measurement of mechanical vibrations - Powell Villena, Andrade (2005)
The wealth of details that optical techniques provide has accelerated their diffusion in various applications of experimental mechanics, with emphasis on non-destructive testing techniques. As part of the recent acquisitions of laboratory material, within the framework of a technological innovation project, an optical Doppler laser velocimetry equipment has been implemented in the Civil Engineering Physics laboratory, which allows measuring the spectral response to vibrations of various structures and constitutes a powerful optical metrology tool.